2021
DOI: 10.1037/vio0000364
|View full text |Cite
|
Sign up to set email alerts
|

Is delinquency associated with subsequent victimization by community violence in adolescents? A test of the risky behavior model in a primarily African American sample.

Abstract: Objective: Victimization is common in adolescence and is associated with negative outcomes, including school failure, and poor emotional, behavioral, and physical health. A deeper understanding of the risk of victimization can inform prevention and intervention efforts. This study tests the risky behavior model in adolescents, examining prospective associations between mean levels of and changes in delinquency and risk for victimization over four annual data collections. Method: Low-income adolescent (53.6% fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Alternatively, it may mean that support for the risky behavior model might be isolated to a particular sociodemographic group, such as adolescents. For example, support for the risky behavior model has been found in a sample of urban African‐American youth (Bountress, 2021). As this study and others have found support for the risky behavior model in earlier developmental periods (e.g., adolescence, Thompson et al, 2017), it may also be that AUD precedes PTSD primarily in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it may mean that support for the risky behavior model might be isolated to a particular sociodemographic group, such as adolescents. For example, support for the risky behavior model has been found in a sample of urban African‐American youth (Bountress, 2021). As this study and others have found support for the risky behavior model in earlier developmental periods (e.g., adolescence, Thompson et al, 2017), it may also be that AUD precedes PTSD primarily in adolescence.…”
Section: Discussionmentioning
confidence: 99%